Teaching for Equity, Justice, and Antiracism with Digital Leteracy Practices : Knowlege, Tools, and Strategies for the ELA Classroom - Barnes, Meghan E.; Marlatt, Rick (Routledge, 2024)
To embrace today’s culturally and linguistically diverse secondary English Language Arts (ELA) classrooms, this text presents ways in which teachers can use digital tools in the service of antiracist teaching and developing equity-oriented mindsets in teaching and learning.